The Effect of Combination Foot Massage and Lemon Aromatherapy on Fatigue Levels in Chronic Kidney Desease Patients Undergoing Hemodialysis - Rahayu, Sri; Sucipto, Ade; Nurrizky, Eki Qarismayah (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Chronic kidney desease is a gradual decline in kidney function over more than 3 months, characterized by a decrease in glomerular filtration rate and an increase in blood creatinine levels. One of the management strategies is hemodialysis, which can cause side effects such as fatigue. Fatigue can interfere with daily activities and is characterized by feelings of weakness, tiredness, lethargy, decreased concentration, emotional disturbances, and sleep disorders. One non-pharmacological therapy to address fatigue is foot massage and lemon aromatherapy, which can provide relaxation effects and influence endorphin hormones, thus reducing fatigue. Objective to determine the effect of the combination of foot massage and lemon aromatherapy on fatigue in patients with chronic kidney failure undergoing hemodialysis at Sultan Imanuddin Regional General Hospital, Pangkalan Bun. This study used a quasi-experimental design with a one-group pretest and posttest approach. The sampling technique was purposive sampling, with 30 respondents participating in the study. The treatment was administered for 10 minutes after the respondents underwent hemodialysis. The research instrument used was the FSS (Fatigue Severity Scale) questionnaire. Before receiving foot massage and lemon aromatherapy, all 30 respondents (100%) experienced fatigue. After the intervention, 27 respondents (90%) no longer experienced fatigue. Statistical analysis using the Wilcoxon test revealed a p-value of 0.000, indicating that p-value < 0.05. The combination of foot massage and lemon aromatherapy has an effect on reducing fatigue in patients with chronic kidney desease undergoing hemodialysis at Sultan Imanuddin Regional General Hospital, Pangkalan Bun.